Hungarian Monitoring, 24 April 1988 . [Magyar rádiófigyelő], 1988. április 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - French presidential elections - Negligence at the Chernobyl atomic reactor - Schultz's talks in the USSR - American-Iranian Gulf War Domestic Affairs: - Party committees in session: need for change of personnel - Peace movement discussions - Situation of Hungarian refugees from Transylvania - Kazinczy prizes awarded Külpolitika: - Francia elnökválasztás - Hanyagság a csernobili atomreaktorban - Schultz tárgyalásai a SZU-ban - Amerikai-iráni öbölháború Belpolitika: - Pártbizottsági ülések: személycserékre van szükség - Békemozgalmi tanácskozás - Erdélyi menekültek helyzete - Átadták a Kazinczy - Díjakat